FUNGAL PATHOGENS CAUSING OTOMYCOSIS AT THE DEPARTMENT OF OTORHINOLARYNGOLOGY, TRA VINH GENERAL HOSPITAL, 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: Determine the distribution of pathogenic gungi and the associated factors among patients with otitis externa presenting to the Otorhinolaryngology Department of Tra Vinh General Hospital.Methods: A descriptive cross-sectional study was conducted from May 2025 to July 2025 among patients with otitis externa who presented to the Otorhinolaryngology Department of Tra Vinh General Hospital. A direct microscopic examination was considered positive for yeast-like fungi when pseudohyphae and/or numerous yeast cells were observed; for filamentous fungi, septate branching hyphae were identified. The causative fungal species were identified based on morphological characteristics.Results: The prevalence of fungal otitis externa was 45.9%. Among the isolated fungi, Candida spp. accounted for 50%, Aspergillus spp. for 30.4%, and Trichophyton spp. for 4.4%; mixed infection with Candida spp. and Aspergillus spp. accounted for 15.2%. Patients presenting with ear itching and tinnitus had a higher prevalence of fungal otitis externa, with prevalence ratios of 2.29 and 1.91, respectively, compared with those without these symptoms (p < 0.05).Conclusion: Fungal otitis externa showed a relatively high prevalence (45.9%), with Candida spp. and Aspergillus spp. being the predominant causative agents, and was significantly associated with clinical symptoms such as ear itching and tinnitus.
Keywords: otomycosis, Candida spp., Aspergillus spp., Tra Vinh General Hospital